2008
DOI: 10.1080/08880010701773738
|View full text |Cite
|
Sign up to set email alerts
|

ZINC STATUS IN PATIENTS WITH MAJOR Β-Thalassemia

Abstract: To determine the zinc status in patients with major beta-thalassemia and its effect on their growth, the authors studied 64 thalassemic patients in comparison with 64 healthy matched individuals. Demographic and anthropometric data and history of the therapies were collected. Serum zinc level in both groups and ferritin in the thalassemic group were assigned. Interestingly, mean serum zinc level was significantly higher in the thalassemic group. No significant correlation between serum zinc level and short sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
35
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 25 publications
9
35
3
Order By: Relevance
“…The findings of the present study showed that the mean serum zinc level of Hb-E â thalassemia group was almost identical with 12 . Sharply contrasting with these findings in Egyptian study showed that there was significantly lower level of zinc in thalassemic population than that in the normal children where serum zinc level was 88.3±17.7 µg/dl vs. 113.5±15.4 µg/dl respectively 21 .…”
Section: Resultssupporting
confidence: 57%
See 4 more Smart Citations
“…The findings of the present study showed that the mean serum zinc level of Hb-E â thalassemia group was almost identical with 12 . Sharply contrasting with these findings in Egyptian study showed that there was significantly lower level of zinc in thalassemic population than that in the normal children where serum zinc level was 88.3±17.7 µg/dl vs. 113.5±15.4 µg/dl respectively 21 .…”
Section: Resultssupporting
confidence: 57%
“…These findings are almost consistent with the findings of Rahman and Jamal 3 . However, Mehdizadeh et al 12 in a similar study reported a higher mean age in their study (164±69.6 months). The difference between Hb-E â thalassemia and control groups in terms of consanguinity of marriage was negligible (10% vs. 3%) and is staggeringly low compared with Shiraj's study conducted in Iranian population where >40% of patients of â thalassemia major had consanguinity of marriage 20 .…”
Section: Resultsmentioning
confidence: 38%
See 3 more Smart Citations